Amphoteric natural starch-coated polymer nanoparticles with excellent protein corona-free and targeting properties. Issue 10 (18th February 2020) - Huang, Bo; Yang, Zhenxing; Fang, Senbiao; Li, Yan; Zhong, Zicheng; Zheng, Ruoqian; Zhang, Jinzhi; Wang, Hangxing; Wang, Suxiao; Zou, Qichao; Wu, Limin
Abstract : Novel amphoteric starch-stabilized nanoparticles exhibit excellent protein corona-free properties and also functionalized by antibodies to achieve excellent targeting and cell internalization capabilities for their use in photodynamic therapy. Abstract : The protein corona on nano drug carriers is an important well-known biological issue that often induces biological incompatibility and screens the targeting molecules on the surfaces of carriers, thus causing a loss of targeting specificity. Although polyethylene glycol (PEG) and zwitterionic polymers have been widely used as anti-fouling materials, there still remain critical challenges for their use as protein-corona agents for drug delivery and targeting. Here, we have designed novel amphoteric natural starch-stabilized core–shell colloidal nanoparticles with more efficient protein corona-free properties, under long term circulation, at different protein concentrations and in different protein charge environments, compared to typical anti-fouling materials such as PEG and zwitterionic polymers. More importantly, the starch-coated polymer nanoparticles can be further functionalized by antibodies to achieve additional excellent targeting and cell internalization capabilities for their use in photodynamic therapy. Our findings demonstrate a novel protein-free or anti-fouling natural material that is very promising for use as highly efficient nano drug carriers and marine coatings.